Karakteristik Operasional Angkutan Ojek Sebagai Angkutan Feeder Perumahan Bukit Lateri Indah, Kota Ambon - Sammyles G. M. Amaheka (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
There is limited public transportation that serves the community from this housing to the destination, so a Feeder transportation is needed. The most commonly used feeder transportation in Ambon City is the motorcycle taxi. The purpose of this study is to analyze the operational characteristics of motorcycle taxi transportation as feeder transport for Bukit Lateri Indah housing, Ambon City. The data analysis technique is by comparing the existing conditions in the field with motorcycle taxi characteristics such as operational characteristics, financial characteristics and income levels. The results showed that the operating time was flexible, but most (95%) motorcycle taxi drivers operated for 15 hours. For the operational capacity of the ojek base, it is known that in 1 hour the base can serve as many as 105 people. As for the pattern of operation, the majority (80%) chose the pattern of operation by stopping by using a queuing system according to the time of arrival by noting it on the blackboard. Waiting time for motorcycle taxis at home 1-5 minutes 70% and at the base 1-5 minutes 100%. For the level of safety obtained that 70% of ojek passengers answered quite well. The level of comfort obtained is that 85% of ojek users feel quite comfortable. The financial feasibility of motorcycle taxi drivers in residential areas in BLI housing is for rental vehicles using the NPV parameter of IDR 6,496,500.00 per year, and using the BCR parameter is 1.33. Whereas for credit vehicles using the NPV parameter is IDR 8,488,000.00, and using the BCR parameter is 1.47.